2020
DOI: 10.1093/mnras/staa3691
|View full text |Cite
|
Sign up to set email alerts
|

Testing physical models for cosmic ray transport coefficients on galactic scales: self-confinement and extrinsic turbulence at ∼GeV energies

Abstract: The microphysics of ∼ GeV cosmic ray (CR) transport on galactic scales remain deeply uncertain, with almost all studies adopting simple prescriptions (e.g. constant-diffusivity). We explore different physically-motivated, anisotropic, dynamical CR transport scalings in high-resolution cosmological FIRE simulations of dwarf and ∼L* galaxies where scattering rates vary with local plasma properties motivated by extrinsic turbulence (ET) or self-confinement (SC) scenarios, with varying assumptions about e.g. turbu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 176 publications
(200 reference statements)
5
83
3
Order By: Relevance
“…Streaming and diffusion are fully-anisotropic along magnetic field lines. In Chan et al (2019) and Hopkins et al (2019Hopkins et al ( , 2021c, we showed that matching observed γ -ray luminosities in simulations with the physics above requires κ CR ∼ 10 29 cm 2 s −1 , in good agreement with detailed CR transport models that include an extended gaseous halo around the Galaxy (see e.g. Strong & Moskalenko 1998;Strong et al 2010;Trotta et al 2011), so we adopt this as our fiducial value.…”
Section: Form Of Jet Energysupporting
confidence: 73%
See 1 more Smart Citation
“…Streaming and diffusion are fully-anisotropic along magnetic field lines. In Chan et al (2019) and Hopkins et al (2019Hopkins et al ( , 2021c, we showed that matching observed γ -ray luminosities in simulations with the physics above requires κ CR ∼ 10 29 cm 2 s −1 , in good agreement with detailed CR transport models that include an extended gaseous halo around the Galaxy (see e.g. Strong & Moskalenko 1998;Strong et al 2010;Trotta et al 2011), so we adopt this as our fiducial value.…”
Section: Form Of Jet Energysupporting
confidence: 73%
“…Because the CR energy density is much larger than kinetic energy density, the CR jet cocoon covers a wider angle (as expected), and can therefore more efficiently suppress inflow. If the CR losses are negligible and CRs become quasi-isotropic, with an effective isotropically averaged diffusivity κ (which includes streaming+advection), then as shown in various studies (Butsky & Quinn 2018;Hopkins et al 2019Hopkins et al , 2021aJi et al 2020) the CR pressure for steady-state injection is P CR (r) ∼ ĖCR /12π κ r. Comparing the outward acceleration ρ −1 ∇P to gravity (∼ v 2 c /r), where v c is the circular velocity, CR pressure alone can support the gas if ĖCR 10 43 erg s −1 10 29 κ n gas 0.01 cm −3 r 30 kpc v c 500 km s −1 2 (15) (where we recall the cooling radius is ∼ 30 kpc here and the diffusivity used here is 10 29 cm 2 s −1 ; see Chan et al 2019;Hopkins et al 2019Hopkins et al , 2021c. This roughly explains the required CR energetics we find in our simulations, as well as the radii/densities where CR pressure dominates for a given ĖCR .…”
Section: Why the Cr Jet Quenches Star Formation More Efficientlymentioning
confidence: 99%
“…For instance, when CRs enter the CGM where gas number densities, magnitudes of magnetic fields and strengths of turbulence are lower, CRs might become less confined and escape from galaxy haloes more quickly than what we see in our CR+ runs. In Hopkins et al (2020b) we have already shown that observationally allowed diffusion coefficients that scales with physical properties of the gas typically leads to properties of galaxies intermediate between MHD and CR+. As a consequence, the level of CR pressure dominance in the CGM and the impact of CRs on the formation of virial shocks in our simulations might change with more realistic CR transport treatments.…”
Section: O N C L U S I O N S a N D Discussion Smentioning
confidence: 94%
“…As a result, there are substantial degrees of freedom in setting the diffusion coefficients and streaming speeds, which can lead to dramatically different outcomes and hence substantial uncertainties (e.g. Hopkins et al 2021c).…”
Section: Introductionmentioning
confidence: 99%